A seven-year electroretinography follow-up of a patient with melanoma-associated retinopathy stabilized on pembrolizumab treatment - Raz Tshuva-Bitton; Michael Ostrovsky; Vicktoria Vishnevskia-Dai; Nancy Agmon-Levin; Ifat Sher; Ygal Rotenstreich (American Journal of Ophthalmology Case Reports)
Purpose: Melanoma-associated retinopathy (MAR) is a rare, auto-immune paraneoplastic syndrome associated with metastatic melanoma. Over the last decade, patient survival has improved dramatically, mainly due to the development of immunotherapy. However, data on long-term MAR patient follow-up and response to modern standard-of-care treatment are lacking. This single-patient case report presents a seven-year, multimodal follow-up of a young MAR patient treated with immune-checkpoint inhibitors. Observations: A 46-year-old Israeli male with a history of cutaneous malignant melanoma presented with sudden onset of bilateral shimmering, flickering, and nyctalopia a year and a half after diagnosis. Shortly thereafter, new subcarinal metastasis was observed on Positron Emission Tomography–Computed Tomography. Significantly reduced electroretinography (ERG) a- and b-wave responses led to a diagnosis of MAR, later confirmed by high titers of autoantibodies against retinal bipolar cells. Half a year later, macular thinning, particularly within the inner nuclear and inner plexiform layers of the outer macular ring, with no substantial change in the outer retina, was observed on optical coherence tomography (OCT). A treatment regimen combining intravenous immune globulin, azathioprine, and prednisone allowed partial steroid tapering over the following 2.5 years but showed substantial toxicity and a lack of significant improvement on OCT and ERG. Pembrolizumab treatment was initiated following metastatic progression and resulted in stabilization of the patient's primary oncologic disease, as well as an increase in macular thickness and enhanced retinal function with an increase of over 60 % in dark adapted (DA) b-wave response over the following year. Conclusions and importance: MAR may be the first sign of systemic metastatic melanoma, thus warranting a high degree of clinical suspicion. While OCT and ERG showed mostly concordant results over the patient's follow-up, ERG proved to be a more sensitive tool for the early diagnosis of MAR. Early immunotherapy treatment should be considered in antibody-positive MAR patients.